Pineapple leaves juice characterization for microbial growth inhibition - Ya'acob, A.; Zainol, N.; Mohd Ridza, P. N. Y.; Mortan, S. H. (IOP Publishing, 2021)
Since pineapple leaves are one of the lavishly organic waste materials which contain phenolic compounds with antimicrobial properties, it was desired to gain deeper knowledge on its potential as microbial growth inhibitor (MGI). In this research, the pineapple leaves were extracted using an electrical sugarcane pressing machine to acquire the pineapple leaves juice (PLJ). The PLJ was autoclaved at 121 °C for 15 min. Ultra-high-performance liquid chromatography-quadrupole time of flight mass spectroscopy (UPLC-QTOF-MS) analysis was used to examined the existence of different bioactive components in PLJ. Based on the molecular mass and its fragmentation pattern, the identification of the phenolic compounds was confirmed. From the characterization of PLJ using UPLC-QTOF-MS, seven types of the phenolic compound has been identified namely Octahydrocurcumin, Meliadanoside A, Kukoamine A, Stilbostemin D, Agrimol C, Feralolide and Methyl-5-O-caffeoylquinate. The effect of microbial inhibition time on the colony forming unit (CFU) between the mixtures of PLJ and microbe was studied. CFU/mL decreased with increasing microbial inhibition time from 0 to 1.50 h. Meanwhile, CFU/mL was increased again after increasing the microbial inhibition period from 1.50 to 3 h. This suggests that 1.50 h was necessary for the process of microbial growth inhibition. This research shows that pineapple leaves could be manipulated and used as an MGI agent as useful sources of natural products. Furthermore, it can become one of the cheaper and greener MGI alternatives compared to available synthetic antimicrobial agent.